Frida Solomonivna Leont’eva - «SISJP NAMS», Staff of SI (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The article is devoted to the well-known specialist in the field of clinical laboratory diagnostics, scientist-biochemist, head of the department of laboratory diagnostics and immunology in Sytenko Institute of Spine and Joint Pathology of NAMS Leontyeva Frida Solomonovna celebrated May 12, 2016 her Anniversary.